Pengaruh Metode Pembelajaran Discovery Learning Menggunakan Media Quizlet untuk Meningkatkan Minat Belajar Siswa dalam Mata Pelajaran IPA di SMP Negeri 3 Kuningan - Pramono, Riskika Arbintang; Lutfi, Ahmad Fajri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine students' learning interest in using the discovery learning method using Quizlet in science at SMP Negeri 3 Kuningan. The learning process is difficult to understand and monotonous, making students feel uninterested. Therefore, a reconstruction of the learning approach is needed, including the application of the discovery learning method using Quizlet to increase student learning interest. The method used is an experimental method with a quantitative approach. The research design used is a one-group pretest-posttest design. The population in this study was all ninth-grade students of SMP Negeri 3 Kuningan, while the sample used was 34 ninth-grade B students, consisting of 20 boys and 14 girls. The research instrument used in this study was a questionnaire. Data analysis techniques used included validity testing, reliability testing, normality testing, linearity testing, and hypothesis testing